HIGH-PRESSURE PHASES IN A SHOCK-INDUCED MELT VEIN OF THE TENHAM L6 CHONDRITE: CONSTRAINTS ON SHOCK PRESSURE AND DURATION - Xie Z.; Sharp T.G.; DeCarli P.S. (My University, 2006)
The microtexture and mineralogy of a 580-?m-wide melt vein in the Tenham L6 chondrite were investigated using field-emission scanning electron microscopy and transmission electron microscopy to better understand the shock conditions. The melt vein consists of a matrix of silicate plus metal-sulfide grains that crystallized from immiscible melts, and sub-rounded fragments of the host chondrite that have been entrained in the melt and transformed to polycrystalline high-pressure silicates. The melt-vein matrix contains two distinct textures and mineral assemblages corresponding to the vein edge and interior. The 30-?m-wide vein edge consists of vitrified silicate perovskite + ringwoodite + akimotoite + majorite with minor metal-sulfide. The 520-?m-wide vein interior consists of majorite + magnesiow?stite with irregular metal-sulfide blebs. Although these mineral assemblages are distinctly different, the pressure stabilities of both assemblages are consistent with crystallization from similar pressure conditions: the melt-vein edge crystallized at about 23-25 GPa and the vein interior crystallized at about 21-25 GPa. This relatively narrow pressure range suggests that the melt vein either crystallized at a constant equilibrium shock pressure of ?25 GPa or during a relatively slow pressure release. Using a finite element heat transfer program to model the thermal history of this melt vein during shock, we estimate that the time required to quench this 580-?m-wide vein was ?40 ms. Because the entire vein contains high-pressure minerals that crystallized from the melt, the shock-pressure duration was at least 40 ms. Using a synthetic Hugoniot for Tenham and assuming that the sample experienced a peak-shock pressure of 25 GPa near the impact site, we estimate that the Tenham parent body experienced an impact with collision velocity ?2 km/s. Based on a one-dimensional planar impact model, we estimate that the projectile size was >150 m in thickness. ? 2005 Elsevier Inc. All rights reserved.
Keywords: CHONDRITE; SHOCK METAMORPHISM